Design and fabricate test rig for kicking soccer ball - Mohd Ridwan, Kasim (2013)
This project presents the development of the test rig for kicking soccer ball. By kicking soccer ball, deformation and velocity of the ball can be calculated. Several players are chosen kicking ball in test. At this rate, the problem occurs when human cannot achieve constant velocity when kicking the ball. The force produced by human is change due to single time. Besides that, human also has limit which is fatigue if continuously doing the same things in several time. The objective is to design and fabricate new test rig for kicking soccer ball and to analyze the experiments of test rig kicking soccer ball. In market, there are several products that have purpose kicking soccer ball such as “Soccer player automaton” and “Adidas rig kicking”. There are built in different moving application. There are seven processes involved which is measuring, marking, cutting material with accurate measuring, drilling and milling, welding and painting. After finish the fabrication process, analysis will be take view in order to candidate the design. In the experiments, test rig will be focused on deformation and velocity of the ball. Maximum deformation was calculated when the initial ball change directly by absorb impact force and then release the ball back into it original shape. Ball velocity was calculated when the ball is moving once got the impact force between foot and ball. The result shows that the maximum deformation and maximum velocity are 11 mm and 6.09 m/s respectively. As the conclusion, the test rig kicking socccer is achieve the objective. There are severals recommendation to improve the products into some high level application of development more effective sports testing products in the future.